Managers’ knowledge and perceptions of the firm’s HIV/AIDS policy and programme - Mabuza, Mbuso (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.